2014
DOI: 10.1002/anie.201409629
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis, Stereochemical Reassignment, and Biological Evaluation of (−)‐Lyngbyaloside B

Abstract: (-)-Lyngbyaloside B is a 14-membered macrolide glycoside isolated from the marine cyanobacterium Lyngbya sp. as a cytotoxic substance by Moore and co-workers. The first total synthesis of (-)-lyngbyaloside B and the reassignment of its stereostructure is described. The synthesis features an Abiko-Masamune aldol reaction, a vinylogous Mukaiyama aldol reaction, and a macrocyclization involving an acyl ketene intermediate for the construction of the macrocyclic backbone, which contains an acylated tertiary alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…79 Additionally, total synthesis and stereochemical reassignment of (À)-lyngbyaloside B, a structure analogue of aurisides, were recently reported by Fuwa et al, wherein a glycosyl trichloroacetimidate was used as the key glycosylation step. 80 Vicenistatin (23) 81,82 In Kanoh's synthesis, the Mukaiyama protocol (with SnCl 2 -AgClO 4 as the promoter) was found not to be reproducible, therefore, the glycosylation of polyene lactam 25 with 2-deoxy-glycosyl uoride 24 was performed in the presence of TMSOTf; 83 subsequent cleavage of the carbamate under basic conditions delivered vicenistatin (23) and its a-anomer in 10% and 18% yield (for two steps), respectively.…”
Section: Syntheses With Glycosyl Fluoridesmentioning
confidence: 99%
“…79 Additionally, total synthesis and stereochemical reassignment of (À)-lyngbyaloside B, a structure analogue of aurisides, were recently reported by Fuwa et al, wherein a glycosyl trichloroacetimidate was used as the key glycosylation step. 80 Vicenistatin (23) 81,82 In Kanoh's synthesis, the Mukaiyama protocol (with SnCl 2 -AgClO 4 as the promoter) was found not to be reproducible, therefore, the glycosylation of polyene lactam 25 with 2-deoxy-glycosyl uoride 24 was performed in the presence of TMSOTf; 83 subsequent cleavage of the carbamate under basic conditions delivered vicenistatin (23) and its a-anomer in 10% and 18% yield (for two steps), respectively.…”
Section: Syntheses With Glycosyl Fluoridesmentioning
confidence: 99%
“…[4] These efforts culminated in the first total synthesis of lyngbyaloside B by Fuwa et al in 2014, in which the stereochemical configuration of lyngbyaloside B was reassigned. [4f] However, previous synthetic endeavors all focused on the lyngbyalosides which possess the (E,E) diene appendage (lyngbouilloside and lyngbyaloside B). Lyngbyaloside B also contains an additional methyl stereogenic center at C6.…”
mentioning
confidence: 99%
“…Yadav et al recently reported a similar strategy towards the synthesis of lyngbyaloside B. [4d] For preparation of the tertiary alcohol, we envisioned the installation of the 1,3- syn diol through utilization of an electrophilic-induced ether transfer methodology recently developed in our labs. [5] The alkene required for the subsequent RCM step provided us with an opportunity to explore a unique ether transfer substrate which contains potentially competing 1,1-disubstituted and terminal alkenes.…”
mentioning
confidence: 99%
“…In 2014, Fuwa and coworkers 7 completed an elegant total synthesis of (−)-lyngbyaloside B, employing innovative use of an Abiko–Masamune anti- aldol and a vinylogous Mukaiyama to install the requisite stereochemistry in the starting building blocks. In this work, synthetic, spectroscopic and molecular modeling studies provided unequivocal stereochemical reassignment of (−)-lyngbyaloside B having epimeric stereogenic centers at C10/C11 and C13 as shown for the reassigned lyngbyaloside B ( 2b ) (Figure 1) when compared with the original assigned structure of lyngbyaloside B ( 2a ).…”
mentioning
confidence: 99%
“…7 Highlights of the synthesis include a phosphate tether-mediated, one-pot, sequential RCM/CM/chemoselective hydrogenation reaction, Roskamp homologation, and a high yielding Boeckman acylketene cyclization. Overall, the synthesis is highly modular and will enable analog synthesis.…”
mentioning
confidence: 99%